High-porosity silicon-bonded silicon carbide easy to extrude and mold and preparation method of high-porosity silicon-bonded silicon carbide

By optimizing the aggregate particle size and pore-forming agent types, the porosity and extrusion performance of high-porosive silicon combined with silicon carbide are improved, and the problems of degradation of molding performance and cracking in the existing technology are solved, thereby achieving high porosity and low thermal expansion coefficient. product.

CN119118680AInactive Publication Date: 2024-12-13YIXING PRINCE CERAMICS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411152322.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when increasing the porosity of diesel vehicle exhaust emission carriers, a large amount of pore-forming agent is required to cause problems such as degradation of molding performance, cracking of products and low pore size.

Method used

By optimizing the particle size of the aggregate, increase the average particle size of 3-6μm SiC fine particles with 5-11%, and use starch to replace it with plastic pore-making agents with better fluidity, adjust the binder and sintering agent formulas, and improve the carrier. base porosity and extrusion properties.

Benefits of technology

A high-pore silicon combined with silicon carbide product with a carrier porosity of more than 60% is achieved, which reduces the amount of pore-forming agent added, improves the extrusion performance and pore size of the product, reduces cracking problems, and reduces the coefficient of thermal expansion and back pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The preparation method comprises the following steps: optimizing the particle size matching of aggregates, increasing 5-11% of SiC fine particles with the average particle size of 3-6 microns, and improving the basic porosity of a carrier by more than 5.5%, so that the addition amount of a pore forming agent required by a unit strip with the porosity of more than 60% is less than 26%; the problem of product cracking caused by the coke discharge amount is greatly reduced, by changing the type of the pore-forming agent, starch is changed into a plastic pore-forming agent with better fluidity, so that the pug extrusion performance of a high-porosity product is equivalent to the pug extrusion performance when the pore-forming agent is not added, and the extrusion length per hour is 23-25m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of honeycomb ceramics, and in particular to high-porosity silicon-bonded silicon carbide that is easy to extrude and a preparation method thereof. Background Art

[0002] The development of the industrialization of the automobile industry has brought about increasingly serious exhaust pollution. As the control standards for automobile exhaust emissions become increasingly stringent, countries around the world, including China, are also increasingly strict with diesel vehicle exhaust emissions. SiC materials are widely used in various fields due to their high temperature strength, good oxidation resistance, wear resistance, good thermal stability, small thermal expansion coefficient, high thermal conductivity, high hardness and other excellent properties.

[0003] In order to meet ultra-low emissions and reduce tail gas pollution, the post-treatment system will be more complicated, so it is necessary to further improve the porosity and pore size of the DPF carrier and reduce its thermal expansion coefficient. In order to increase the porosity of the carrier to more than 60%, a large proportion of pore-forming agent needs to be added. If pore-forming agents such as starch and shell powder commonly used in the industry are used, the amount of pore-forming agent added often needs to be greater than 33%.

[0004] A large amount of pore-forming agent can easily lead to the following problems: (1) the molding performance of the mud material is greatly reduced, and the production efficiency is reduced; (2) when the pore-forming agent is removed, it is easy to produce violent coking, which may cause the product to crack; (3) at the same time, the higher coking temperature will lead to a lower pore size in the product, making the product back pressure drop less than expected. Summary of the invention

[0005] Purpose of the invention:

[0006] In order to overcome the problems existing in the prior art, the present invention provides a high-porosity silicon-bonded silicon carbide that is easy to extrude and a preparation method thereof. By optimizing the aggregate size combination, 5 to 11% of SiC fine particles with an average particle size of 3 to 6 μm are added, and the basic porosity of the carrier is increased by more than 5.5%, so that the amount of pore-forming agent required for unit bars with a porosity of more than 60% is less than 26%, thereby greatly reducing the problem of product cracking caused by the amount of coke discharge.

[0007] To solve the above problems, the present invention adopts the following technical solutions:

[0008] A highly porous silicon-bonded silicon carbide that is easy to extrude and mold, wherein the silicon carbide raw materials include aggregate, pore former, binder, active agent and sintering agent;

[0009] The aggregate comprises, by weight, 64 to 77 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm; 5 to 11 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm; and 18 to 25 parts of metallic silicon with an average particle size of 7 to 13 μm.

[0010] Preferably, the pore former comprises 0-15% starch by weight of the aggregate, with an average particle size of 25-35 μm, 5-20% nylon resin beads, with an average particle size of 18-28 μm, and 3-6% super absorbent resin beads, with an average particle size of 33-38 μm.

[0011] Preferably, the pore former accounts for 8% to 26% of the weight of the aggregate.

[0012] Preferably, the binder comprises 5-9% of methyl cellulose and 2-6% of polyvinyl alcohol aqueous solution based on the weight of the aggregate.

[0013] Preferably, the active agent includes 0-4% glycerol and 0-2% potassium laurate based on the weight of the aggregate.

[0014] Preferably, the sintering agent includes 0.5-4% clay-type kaolin or bentonite, 0-3% alumina, and 0-2% strontium carbonate or calcium carbonate, based on the weight of the aggregate.

[0015] The present invention also proposes a method for preparing high-porosity silicon-bonded silicon carbide that is easy to extrude and mold, comprising the following steps:

[0016] S1. Batching: Aggregate, pore former, binder, active agent and sintering agent are mixed according to the weight of the formula, mechanically stirred in a mixer for 20 to 60 minutes, and then extruded and kneaded in a mud mill for 20 to 60 minutes to form slurry mud;

[0017] S2, extrusion molding: according to the design requirements, a multi-channel mold of a certain shape is processed and installed at the head of the extruder, the slurry mud is added into the silo of the extruder, and then the embryo body of the designed shape is extruded;

[0018] S3, debinding and sintering: debind the embryo at 400-500°C for 2-4h; then sinter in an oxygen-free atmosphere at 1420-1450°C for 2-4h; finally oxidize at 1100-1250°C under aerobic conditions for 1-3h to obtain high-porosity silicon-bonded silicon carbide.

[0019] Preferably, the aggregate is prepared by ball-milling coarse silicon carbide particles, fine silicon carbide particles and metallic silicon, using alumina grinding balls, with a weight ratio of 1:2 and a material-water ratio of 4:3, and the aggregate is generated after ball-milling for 2 to 8 hours.

[0020] Preferably, in step S2, the extrusion speed of the extruder is 20 to 25 Hz.

[0021] Preferably, the binder is prepared by mixing clay-based kaolin or bentonite, alumina, strontium carbonate or calcium carbonate and ball-milling the mixture, wherein the ball-milling medium is anhydrous ethanol, and the ball-milling time is 24 to 48 hours to generate the binder.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0023] 1. By optimizing the aggregate size, the average particle size of 3-6μm SiC fine particles is increased by 5-11%, and the basic porosity of the carrier is increased by more than 5.5%, so that the amount of pore former required for the unit bar with a porosity of more than 60% is less than 26%, which greatly reduces the product cracking problem caused by the amount of coke discharge.

[0024] 2. By changing the type of pore-forming agent from starch to plastic pore-forming agent with better fluidity, the extrusion performance of the high-porosity product is equivalent to that of the clay extrusion performance without adding pore-forming agent, and the extrusion length per hour is 23 to 25 meters.

[0025] 3. The unit bars prepared by this method have a higher pore size, a lower thermal expansion coefficient and a lower back pressure. DETAILED DESCRIPTION

[0026] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below.

[0028] A highly porous silicon-bonded silicon carbide that is easy to extrude and mold, wherein the silicon carbide raw materials include aggregate, pore former, binder, active agent and sintering agent;

[0029] The aggregate comprises, by weight, 64 to 77 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm; 5 to 11 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm; and 18 to 25 parts of metallic silicon with an average particle size of 7 to 13 μm.

[0030] The pore-forming agent includes starch accounting for 0-15% of the aggregate weight, with an average particle size of 25-35 μm, nylon resin beads accounting for 5-20% of the aggregate weight, with an average particle size of 18-28 μm, and high water-absorbent resin beads accounting for 3-6% of the aggregate weight, with an average particle size of 33-38 μm.

[0031] The pore-forming agent accounts for 8% to 26% of the weight of the aggregate.

[0032] The binder comprises 5-9% of methyl cellulose and 2-6% of polyvinyl alcohol aqueous solution, accounting for 5-9% of the weight of the aggregate.

[0033] The active agent comprises 0-4% glycerol and 0-2% potassium laurate, accounting for the weight of the aggregate.

[0034] The sintering agent includes 0.5-4% clay kaolin or bentonite, 0-3% alumina, and 0-2% strontium carbonate or calcium carbonate, accounting for 0.5-4% of the weight of the aggregate.

[0035] The present invention also proposes a method for preparing high-porosity silicon-bonded silicon carbide that is easy to extrude and mold, comprising the following steps:

[0036] S1. Batching: Aggregate, pore former, binder, active agent and sintering agent are mixed according to the weight of the formula, mechanically stirred in a mixer for 20 to 60 minutes, and then extruded and kneaded in a mud mill for 20 to 60 minutes to form slurry mud;

[0037] S2, extrusion molding: according to the design requirements, a multi-channel mold of a certain shape is processed and installed at the head of the extruder, the slurry mud is added into the silo of the extruder, and then the embryo body of the designed shape is extruded;

[0038] S3, debinding and sintering: debind the embryo at 400-500°C for 2-4h; then sinter in an oxygen-free atmosphere at 1420-1450°C for 2-4h; finally oxidize at 1100-1250°C under aerobic conditions for 1-3h to obtain high-porosity silicon-bonded silicon carbide.

[0039] Preferably, the aggregate is prepared by ball-milling coarse silicon carbide particles, fine silicon carbide particles and metallic silicon, using alumina grinding balls, with a weight ratio of 1:2 and a material-water ratio of 4:3, and the aggregate is generated after ball-milling for 2 to 8 hours.

[0040] Preferably, in step S2, the extrusion speed of the extruder is 20 to 25 Hz.

[0041] Preferably, the binder is prepared by mixing clay-based kaolin or bentonite, alumina, strontium carbonate or calcium carbonate and ball-milling the mixture, wherein the ball-milling medium is anhydrous ethanol, and the ball-milling time is 24 to 48 hours to generate the binder.

[0042] Embodiment 1:

[0043] The aggregate comprises 71.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, 5 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm, and 23.5 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight; the pore-forming agent comprises 13% of the weight of the aggregate, starch with an average particle size of 25 to 35 μm, 6.5% of nylon resin beads with an average particle size of 18 to 28 μm, and 5.7% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 25.2% of the weight of the aggregate; the sintering agent comprises 1% of bentonite, 1% of alumina, and 2% of strontium carbonate, the binder comprises 5 to 9% of the weight of the aggregate, and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, by weight of the aggregate.

[0044] Embodiment 2:

[0045] The aggregate comprises 73.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, 5 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm, according to weight percentage; the pore-forming agent comprises 9.8% of starch with an average particle size of 25 to 35 μm, 9.8% of nylon resin beads with an average particle size of 18 to 28 μm, and 3.9% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 23.5% of the weight of the aggregate; the sintering agent comprises 1% of bentonite, 0.4% of alumina, and 1% of strontium carbonate, which account for 1% of the weight of the aggregate; the binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, which account for 5 to 9% of the weight of the aggregate; and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, which account for 0 to 4% of the weight of the aggregate.

[0046] Embodiment 3:

[0047] The aggregate comprises 76.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, 5 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm, and 18.5 parts of metallic silicon with an average particle size of 7 to 13 μm, according to weight percentage; the pore-forming agent comprises 4.9% of starch with an average particle size of 25 to 35 μm, 14.6% of nylon resin beads with an average particle size of 18 to 28 μm, and 5.7% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 25.2% of the weight of the aggregate; the sintering agent comprises 2% of bentonite, 3% of alumina, and 0% of strontium carbonate, which account for 2% of the weight of the aggregate; the binder comprises 5 to 9% of methyl cellulose and 2 to 6% of polyvinyl alcohol aqueous solution, which account for 5 to 9% of the weight of the aggregate; and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, which account for 0 to 4% of the weight of the aggregate.

[0048] Embodiment 4:

[0049] The aggregate comprises 73.3 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, 8.1 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm, and 18.6 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight. The pore-forming agent comprises 12.2% of starch with an average particle size of 25 to 35 μm, 10.6% of nylon resin beads with an average particle size of 18 to 28 μm, and 3% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 25.8% of the weight of the aggregate. The sintering agent comprises 1.6% of bentonite, 0.3% of alumina, and 1.6% of strontium carbonate, by weight of the aggregate. The binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, by weight of the aggregate.

[0050] Embodiment 5:

[0051] The aggregate comprises 68.4 parts of silicon carbide coarse particles with an average particle size of 25 to 35 μm, 6.5 parts of silicon carbide fine particles with an average particle size of 3 to 6 μm, and 25.1 parts of metallic silicon with an average particle size of 7 to 13 μm in parts by weight. The pore-forming agent comprises 4.9% of starch with an average particle size of 25 to 35 μm, 14.7% of nylon resin beads with an average particle size of 18 to 28 μm, and 3.9% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 23.5% of the weight of the aggregate. The sintering agent comprises 0.8% of bentonite, 0.6% of alumina, and 1.3% of strontium carbonate, which account for 0.8% of the weight of the aggregate. The binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, which account for 5 to 9% of the weight of the aggregate. The active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, which account for 0.2% of the weight of the aggregate.

[0052] Embodiment 6:

[0053] The aggregate comprises 68.7 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, 9.8 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight. The pore-forming agent comprises 4.9% of starch with an average particle size of 25 to 35 μm, 14.6% of nylon resin beads with an average particle size of 18 to 28 μm, and 3.9% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 23.4% of the weight of the aggregate. The sintering agent comprises 0.8% of bentonite, 0.4% of alumina, and 1% of strontium carbonate, by weight of the aggregate. The binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, by weight of the aggregate.

[0054] Embodiment 7:

[0055] The aggregate comprises, by weight, 67.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, 11 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm. The pore-forming agent comprises 14.4% of the weight of the aggregate of nylon resin beads with an average particle size of 18 to 28 μm, and 6% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 20.4% of the weight of the aggregate. The sintering agent comprises 0.8% of bentonite, 0.4% of alumina, and 1% of strontium carbonate, which account for 0.8% of the weight of the aggregate. The binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, which account for 5 to 9% of the weight of the aggregate. The active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, which account for 0 to 2% of the weight of the aggregate.

[0056] Comparative Example 1:

[0057] The aggregate comprises 78.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight; no pore-forming agent is added; the sintering agent comprises 0.8% of bentonite, 0.4% of alumina, and 0.4% of strontium carbonate, accounting for 0.8% of the weight of the aggregate; the binder comprises 5 to 9% of methyl cellulose, and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, accounting for 0.8% of the weight of the aggregate.

[0058] Comparative Example 2:

[0059] The aggregate comprises 78.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight. The pore-forming agent comprises 40% of the weight of the aggregate, with an average particle size of 25 to 35 μm, and the total pore-forming agent accounts for 40% of the weight of the aggregate. The sintering agent comprises 0.8% of bentonite, 0.4% of alumina, and 0.4% of strontium carbonate, by weight of the aggregate. The binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, by weight of the aggregate.

[0060] Comparative Example 3:

[0061] The aggregate comprises 78.5 parts of silicon carbide coarse particles with an average particle size of 25 to 35 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight. The pore-forming agent comprises 19% of the weight of the aggregate, with an average particle size of 25 to 35 μm, and 11.5% of nylon resin beads with an average particle size of 18 to 28 μm, and the total pore-forming agent accounts for 30.5% of the weight of the aggregate. The sintering agent comprises 1% of the weight of the aggregate, 0.4% of aluminum oxide, and 0.9% of strontium carbonate, the binder comprises 5 to 9% of the weight of the aggregate, and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, by weight of the aggregate.

[0062] Comparative Example 4:

[0063] The aggregate comprises 78.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm, and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm, by weight. The pore-forming agent comprises 15.4% of starch with an average particle size of 25 to 35 μm, 15.4% of nylon resin beads with an average particle size of 18 to 28 μm, and 4.8% of highly absorbent resin beads with an average particle size of 33 to 38 μm, and the total pore-forming agent accounts for 35.6% of the weight of the aggregate. The sintering agent comprises 1.2% of bentonite, 0.4% of alumina, and 1% of strontium carbonate, by weight of the aggregate. The binder comprises 5 to 9% of methyl cellulose and 2 to 6% of a polyvinyl alcohol aqueous solution, and the active agent comprises 0 to 4% of glycerol and 0 to 2% of potassium laurate, by weight of the aggregate.

[0064] Comparative Example 5:

[0065] The aggregate comprises, by weight, 73.5 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm; 5 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm; and 21.5 parts of metallic silicon with an average particle size of 7 to 13 μm. No pore-forming agent is added. The sintering agent comprises 1% of bentonite, 0.4% of alumina, and 1% of strontium carbonate, accounting for 1% of the weight of the aggregate. The binder comprises 5% to 9% of methyl cellulose and 2% to 6% of a polyvinyl alcohol aqueous solution. The active agent comprises 0% to 4% of glycerol and 0% to 2% of potassium laurate, accounting for 1% of the weight of the aggregate.

[0066] The above embodiments and comparative examples were measured for extrusion time, water absorption, porosity, pressure parallel to the direction of the honeycomb slot (A axis), average pore size, pore volume, and extrusion speed. The same screw extruder was used, and the extrusion motor frequency was set to 20 Hz. The extrusion speed was measured at this frequency. The specific results are shown in the following table:

[0067]

[0068]

[0069] The test results show that by optimizing the aggregate size, adding 5-11% of SiC fine particles with an average particle size of 3-6μm, the basic porosity of the carrier is increased by more than 5.5%, so that the amount of pore formers required for the unit strips with a porosity of more than 60% is less than 26%, which greatly reduces the product cracking problem caused by the amount of coke discharge. By changing the type of pore former, from starch to plastic pore formers with better fluidity, the mud extrusion performance of high-porosity products is equivalent to that of mud extrusion without adding pore formers, with an extrusion length of 23-25m per hour, and at the same time has relatively good water absorption, thermal expansion coefficient, pore size, pore volume and.

[0070] The purpose of the above embodiments is to exemplarily reproduce and deduce the technical solution of the present invention, and to fully describe the technical solution, purpose and effect of the present invention. Its purpose is to make the public understand the disclosed content of the present invention more thoroughly and comprehensively, and it does not limit the scope of protection of the present invention.

[0071] The above embodiments are not exhaustive enumerations of the present invention, and there may be multiple other implementations not listed. Any replacement and improvement made without violating the concept of the present invention shall fall within the protection scope of the present invention.

Claims

1. A highly porous silicon-bonded silicon carbide that is easily extruded, characterized in that: Silicon carbide raw materials include aggregate, pore former, binder, activator and sintering agent; The aggregate comprises, by weight, 64 to 77 parts of coarse silicon carbide particles with an average particle size of 25 to 35 μm; 5 to 11 parts of fine silicon carbide particles with an average particle size of 3 to 6 μm; and 18 to 25 parts of metallic silicon with an average particle size of 7 to 13 μm.

2. The easily extrudable high-porosity silicon-bonded silicon carbide according to claim 1, characterized in that: The pore-forming agent comprises starch accounting for 0-15% of the weight of the aggregate, with an average particle size of 25-35 μm, nylon resin beads accounting for 5-20% of the weight of the aggregate, with an average particle size of 18-28 μm, and highly absorbent resin beads accounting for 3-6% of the weight of the aggregate, with an average particle size of 33-38 μm.

3. The easily extrudable high-porosity silicon-bonded silicon carbide according to claim 1 or 2, characterized in that: The pore-forming agent accounts for 8% to 26% of the weight of the aggregate.

4. The easily extrudable high-porosity silicon-bonded silicon carbide according to claim 1, characterized in that: The binder comprises 5-9% of methyl cellulose and 2-6% of polyvinyl alcohol aqueous solution, accounting for 5-9% of the weight of the aggregate.

5. The easily extrudable high-porosity silicon-bonded silicon carbide according to claim 1, characterized in that: The active agent comprises 0-4% glycerol and 0-2% potassium laurate, accounting for the weight of the aggregate.

6. The easily extrudable high-porosity silicon-bonded silicon carbide according to claim 1, characterized in that: The sintering agent includes 0.5-4% clay kaolin or bentonite, 0-3% alumina, and 0-2% strontium carbonate or calcium carbonate, accounting for 0.5-4% of the weight of the aggregate.

7. A method for preparing a highly porous silicon-bonded silicon carbide that is easily extrudable as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Batching: Aggregate, pore former, binder, active agent and sintering agent are mixed according to the weight of the formula, mechanically stirred in a mixer for 20 to 60 minutes, and then extruded and kneaded in a mud mill for 20 to 60 minutes to form slurry mud; S2, extrusion molding: according to the design requirements, a multi-channel mold of a certain shape is processed and installed at the head of the extruder, the slurry mud is added into the silo of the extruder, and then the embryo body of the designed shape is extruded; S3, debinding and sintering: debind the embryo at 400-500°C for 2-4h; then sinter in an oxygen-free atmosphere at 1420-1450°C for 2-4h; finally oxidize at 1100-1250°C under aerobic conditions for 1-3h to obtain high-porosity silicon-bonded silicon carbide.

8. The method for preparing highly porous silicon-bonded silicon carbide that is easily extrudable according to claim 7, characterized in that: The aggregate is prepared by ball-milling and mixing coarse silicon carbide particles, fine silicon carbide particles and metallic silicon, using alumina grinding balls, with a weight ratio of 1:2 and a material-water ratio of 4:

3. The aggregate is generated after ball-milling and mixing for 2 to 8 hours.

9. The method for preparing highly porous silicon-bonded silicon carbide that is easily extrudable according to claim 8, characterized in that: In step S2, the extrusion speed of the extruder is 20-25 Hz.

10. The method for preparing highly porous silicon-bonded silicon carbide that is easily extrudable according to claim 7, characterized in that: The binder is prepared by mixing clay-type kaolin or bentonite, alumina, strontium carbonate or calcium carbonate and subjecting the mixture to ball milling, wherein the ball milling medium is anhydrous ethanol, and the ball milling time is 24 to 48 hours to generate the binder.

Citation Information

Patent Citations

  • Filter for trapping diesel engine soot particles, and making method thereof

    CN105481367A

  • Method of using heat-conducting zeolite silicon carbide ceramic microbeads to prepare porous water-collecting sponge brick

    CN106187034A

  • Porous silicon carbide ceramic and preparation method thereof

    CN107698276A

  • Method for preparing silicon carbide ceramic filter with pore forming agent adding process

    CN108178655A

  • Multi-channel silicon carbide ceramic membrane support and preparation method thereof

    CN108264354A